Non-Linear Innovation - Shur-Ofry, Michal (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2016)
Contemporary intellectual property theory concentrates on the cumulative and incremental nature of innovation and creation. A prevalent image depicts authors and inventors as “standing on the shoulders of giants.” This article focuses on a different type of innovation that has been largely overlooked by intellectual property theory and doctrine: innovation in the domains of science and art that breaks with convention, disputes existing paradigms, and “steps off” giants’ shoulders. I term it “non-linear innovation”.Drawing on multidisciplinary research ranging from the history of science, through network analysis of radical inventions, to studies of creativity, this article illuminates an embedded socio-cultural preference for incremental and linear novelty over paradigm-changing innovation. It then inquires whether intellectual property doctrine reflects this bias and whether the intellectual property regime can better foster non-linear innovation. The examination yields a series of counterintuitive recommendations concerning numerous patent and copyright law doctrines. More broadly, the analysis indicates that neither the “shoulders of giants” metaphor nor the opposite image of the “lone genius” adequately capture the dynamics of non-linear innovation. It further suggests that expanding intellectual property’s narrative of progress to accommodate non-linear innovation, alongside cumulative innovation, could significantly contribute to the ecosystem of innovation and creation.